The effect of neurofeedback on the reaction time and cognitive performance of athletes: a systematic review and meta-analysis - de Brito, M. A.; Fernandes, J. R.; Esteves, N. S. A.; Müller, V. T.; Alexandria, D. B.; Pérez, D. I. V.; Slimani, M.; Brito, C. J.; Bragazzi, N. L.; Miarka, B. (Frontiers in Human Neuroscience, 2022)
Our study evaluated the effect of training with neurofeedback (NFB) in improving athletes' reaction time and decision-making. A computerized search in PubMed, PsycINFO, Scielo, Web of Science, EMBASE, Scopus, BVS, and Cochrane databases was performed to identify studies published from 2011 to June 2021. The protocol was registered in PROSPERO. The quality of studies that was peer-reviewed and included was assessed using the Review Manager tool, Cochrane Risk of Bias, and design and reporting quality according to the CRED-nf checklist. Standard mean differences and 95% confidence intervals (CIs) were calculated and combined using a random-effects model. A total of 07 randomized controlled trials (RCTs) (173 athletes) met the inclusion criteria. Significant effects of NFB in the experimental group in relation to reaction time were found, indicating an improvement in sports performance [standardized mean difference (SMD) = -1.08; 95% CI = (-1.90, -0.25), p = 0.0009] and cognitive performance vs. decision-making with moderate effect [SMD = 1.12; 95% CI = (-0.40, 1.85), p = 0.0001]. However, the control group had a very small effect on cognitive performance [SMD = 0.19; 95% CI = (-0.20, 0.59), p = 0.086]. NFB could improve athletes' reaction time and decision-making, effectively increasing their performance in the sports field. Future studies should focus on standardized protocols for NFB training.